Studi Literatur: Peran Apoteker dalam Pengawasan Keamanan Vaksin P dan M di Indonesia - Reyhan Diva Zaafira; Windy Amelia; Revita Fitri Amelia; Rosa Adelina (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2022)
Abstract: Coronavirus disease (COVID-19) has infected millions of people globally since the World Health Organization declared a pandemic on March 11, 2020. Various efforts have been made to control the COVID-19 pandemic, including the development of vaccines. Pfizer and Moderna vaccines are mRNA-based vaccines developed in Indonesia with promising safety and effectiveness. The method used in this research is a descriptive method using literature studies in journals that discuss the safety control of P and M vaccines in Indonesia, with work procedures that include literature search, literature selection, literature documentation, analysis, and drawing conclusions. The results of the literature study show that pharmacists play an important role in maintaining the safety, quality, and efficacy of vaccines starting from the selection and procurement of distribution (which includes storage) to the time of use. At the selection stage, pharmacists must be able to consider the policies of international and national organizations. Pharmacists are fully responsible for procurement by ensuring that the vaccines received meet the standards and have a certificate of release from the competent authority of the country where the vaccine was released as well as a summary protocol issued by the manufacturer. Pharmacists are also responsible for distribution by keeping the COVID-19 vaccine within the specified temperature range. In use, pharmacists play a role in ensuring that vaccines are given according to the rules and in post-vaccination Monitoring of Drug Side Effects.